Blockchain Technology: Challenges and Opportunities in the World of Indirect Taxes - et.al, Suhas Saini (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Blockchain Technology revolutionize the market of digitization. Blockchain technology has also emerged as a solution in case of indirect taxes also. This technology can transform the tax regime and can contribute majorly to digital India. In GST a registered firm has to file 37 returns during a year, this technology will reduce this burden off the vendors as all the transactions are recorded in real time in block chain , which removes the need of filing any return. Transparency of system will remove all the loopholes from the system and tax evasion will also become impossible which will ultimately lead to reduction in frauds and a tampered proof system. Blockchain has brought a lot of excitement and this technology has shown its potential to transform business. But what this technology could do for the world of indirect tax? This paper will look at the challenges and opportunities that lies ahead for government in the world of indirect taxes.